Ovarian Fibrothecoma in Mare - Case Report - Kievitsbosch, Thatiane; Prestes, Nereu Carlos [UNESP]; Fabris, Viciany Erique; Scagion Salgado, Luíz Fernando; Alvarenga, Marco Antonio [UNESP] (Elsevier, 2013)
A 5-year-old Mangalarga mare was referred to the Veterinary Teaching Hospital of the Veterinary Medical School in Botucatu with a complaint of a persistent 2-month ovarian follicle which had grown progressively to 20 cm in diameter. Ultrasonography showed a circular, cystic structure in the right ovary, whose wall was thickened and interior was filled with anechoic content. Ovarian neoplasia was suspected, and a unilateral ovariectomy was performed through the paralumbar fossa, using general anesthesia through inhalation. Histopathological evaluation concluded that the ovarian enlargement was caused by a fibrothecoma. The present report describes features of fibrothecoma, which is extremely rare in the equine species. © 2013 Elsevier Inc. All rights reserved.
Keywords: Fibrothecoma; Histopathology; Mare; Ovarian tumor; Ovariectomy